Pengembangan Kreativitas Peserta Didik Melalui Pembelajaran Berbasis Game Pada Mata Pelajaran Pendidikan Agama Islam - Aini Yatul Hajro; Muhammad Rifa’i Subhi (Muaddib: Jurnal Pendidikan Agama Islam, 2023)
Developing students' creativity through game-based learning in Islamic Education subjects is very useful. Learning is a complex process and requires an innovative approach to increase students' creativity. One method that can be used is game-based learning, which is able to combine educational elements with entertainment aspects. This research aims to examine the development of students' creativity through the application of game-based learning in PAI subjects. The research method used is classroom action research involving class students which consists of two learning cycles. The research results show a significant increase in students' creativity levels after participating in game-based learning. This learning provides opportunities for students to develop their creativity through challenges in the form of games that are integrated with the concept of Islamic Religious Education. In addition, students show a high level of motivation in participating in learning, considering that the game element provides a fun and interactive learning experience. This research contributes to educational literature by showing that game-based learning can be an effective alternative in increasing students' creativity in Islamic Religious Education subjects. The practical implication of this research is the need to apply innovative and interesting learning methods to increase the effectiveness of religious learning in schools.